EMOTIONAL INTELLIGENCE’S STRENGTHENS ON AUDIT QUALITY - Ilmawan, Faiz Nuha; Try Setyorini, Christina; Rachmi Fitrijati, Krisnhoe; Rangga Bawono, Icuk (AKUNTANSI DEWANTARA, 2024)
This study aims to analyze emotional intelligence on audit quality with competence as moderation. This study used a quantitative approach. The population in this study is financial auditors in the "Big Four" Public Accountants in Indonesia from the level of partners, managers, seniors, and junior auditors. The results showed that emotional intelligence and competence had a significant positive effect on audit quality. Competence shows unsupported results as moderation on the relationship of emotional intelligence to audit quality. From the results of the study, there are several implications, namely in the recruitment process, PAF should comprehensively consider aspects of EI and competence. In the process of educating prospective auditors, there needs to be material related to emotional intelligence. When carrying out their profession, auditors need to have the awareness to implement EI. In the future, it is recommended to use the interview method so that it can ensure a more objective response from respondent.